1996
DOI: 10.1002/cbf.673
|View full text |Cite
|
Sign up to set email alerts
|

The control of mitochondrial respiration in yeast: A possible role of the outer mitochondrial membrane

Abstract: Mitochondrial respiration in yeast (S. cerevisiae) is regulated by the level of glucose in the medium. Glucose is known to inhibit respiration by repressing key enzymes in the respiratory chain. We present evidence that the early events in this inhibition include the closure of VDAC channels, the primary pathway for metabolite flow across the outer membrane. Aluminum hydroxide is known to inhibit the closure of VDAC. Addition of aluminum acetylacetonate to yeast cells, which should elevate the aluminum hydroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…The major source of ROS in most cell types is the mitochondrion, as by-products of aerobic respiration; therefore, we decided to investigate mitochondrial organization and function during starvation (Murphy, 2009). S. cerevisiae cells growing in glucose actively repress mitochondrial respiration and rely entirely on glycolysis for energy (Ahmadzadeh et al, 1996; Entian and Barnett, 1992). When the carbon source is changed to a nonfermentable one, such as glycerol, ethanol or acetate, cells switch to mitochondrial respiration as the major source of ATP (Boy-Marcotte et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…The major source of ROS in most cell types is the mitochondrion, as by-products of aerobic respiration; therefore, we decided to investigate mitochondrial organization and function during starvation (Murphy, 2009). S. cerevisiae cells growing in glucose actively repress mitochondrial respiration and rely entirely on glycolysis for energy (Ahmadzadeh et al, 1996; Entian and Barnett, 1992). When the carbon source is changed to a nonfermentable one, such as glycerol, ethanol or acetate, cells switch to mitochondrial respiration as the major source of ATP (Boy-Marcotte et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…2). Closure of VDAC channels, the primary pathway for metabolite flow across the outer membrane, has been shown to occur as an early step in the inhibition of respiration by glucose [45]. Since no change in the phosphorylation status of Por1p was observed after the diauxic shift, phosphorylation is probably not involved in VDAC opening or closure.…”
Section: Mitochondrial Outer Membranementioning
confidence: 94%
“…These data agree with studies of porin import into mitochondria isolated from yeast coq5 mutant strains (14) demonstrating that the porin import is independent of Q 6 content or state of respiration. Some studies have indicated that porin is hyperexpressed in stationary phase, upon diauxic shift, and upon glucose deficiency (55,56). Other authors have indicated that the in vitro import of porin to mitochondria does not require ATP (57).…”
Section: Figmentioning
confidence: 99%